Comparative Study of Consumption Theories: The Perspective of John Maynard Keynes and Monzer Kahf - Labolo, Sultan Nanta Setia Dien; Nuarisa, Risma Hafida; Wardani, Petria Wafa Kusuma (Journal of Islamic Economics and Philanthropy, 2024)
This study aims to compare the consumption theories of John Maynard Keynes, a conventional economist, and Monzer Kahf, an Islamic economist. The main objective is to identify the strengths and weaknesses of each approach while emphasizing how both theories contribute to economic growth and stability. This study uses a qualitative methodology, thoroughly analyzing primary and secondary sources on the works of both economists. Through comparative analysis, this study evaluates the core concepts and assumptions of each theory. The findings show that Keynes' approach is concerned with individual consumption and its impact on savings and economic growth, while Kahf's theory encourages consumption for the collective good in accordance with Islamic principles. The study concludes that combining elements of both theories can offer a more balanced approach, which at the same time enhances social welfare and economic stability.